The relationships between managing talent practices, knowledge management and organizational performance of Malaysian private colleges - Khor, Kok Keat (2017)
The purpose of this study was to investigate the organizational performance of private colleges in association with managing talent practices, and to evaluate the mediation role of knowledge management on the relationship between practices of managing talent attraction and recruitment, talent development and talent retention with the organizational performance of private colleges. PLS-SEM technique was deployed to test the hypothesized relationships in the model. A questionnaire was developed with 41 items adapted from previous validated scales. The survey method was used to collect quantitative data for all the variables in the study. The non-probability sampling approach of convenience sampling was utilized. 1300 questionnaires were administered to 260 private colleges in Malaysia. The unit of analysis was at the individual level. Five respondents per college were surveyed and this provided a sample size of 243 representing 49 private colleges. A response rate of 18.7% was achieved. Empirical findings in this study highlighted that managing talent development has a significant positive relationship with the organizational performance of private colleges. Knowledge management has a significant direct positive relationship with the organizational performance of private colleges. The practices of managing talent attraction and recruitment, talent development and talent retention show significant positive influence on knowledge management among private colleges. The mediation effects of knowledge management are statistically significant, and partially mediates the relationship between practices of managing talent attraction and recruitment, talent development and talent retention with respect to the organizational performance of private colleges. The model shows a moderately strong explanatory power, besides making some theoretical and practical contributions.